Elemental indicators of natural and anthropogenic aerosol inputs to Law Dome, Antarctica - Jean-Pierre Candelone; Kevin J.R. Rosman; V. Morgan; Vania Gaspari; K. Van de Velde; G. Cozzi; Paolo Cescon; Paul Vallelonga; Claude F. Boutron; Carlo Barbante (Annals of Glaciology, 2004)
AbstractA selection of elements (Bi, Ca, Cd, Co, Cu, Mn, Na, Sr, U, V, Zn) were measured by high-resolution inductively coupled plasma sector-field mass spectrometry in firn- and ice-core samples from Law Dome, Antarctica, corresponding to the period 4500 BC to AD 1989. Concentrations of rock dust and sea salts were calculated for each sample and then used to determine concentrations of each element originating from crustal and marine aerosol emissions, respectively. Where calculated contributions from crustal and marine aerosol sources failed to account for the total measured concentration of an element, the remainder was apportioned to volcanic and/or anthropogenic sources and defined as an enrichment. On this basis, it was determined that Bi and Cd concentrations in Law Dome ice are overwhelmingly influenced by volcanic emissions (enrichments 150–250x crustal and marine inputs); Co, Cu, Pb and Zn concentrations in Law Dome ice are largely influenced by volcanic emissions (enrichments 16–36x crustal and marine inputs); and Mn, Sr, U and V concentrations in Law Dome ice are minimally influenced by volcanic emissions (enrichments 1.5–4x crustal and marine inputs). During the 20th century, enrichments of Pb and Cu concentrations were observed to be greater than in earlier centuries, consistent with increasing anthropogenic emissions of Pb and Cu in the Southern Hemisphere over that period.